KARAKTERISASI BLOK REM KERETA API BERBAHAN BESI COR DAN Al-SiC BERDASARKAN KEKUATAN UJI TARIK DAN HARGA IMPAK - Senen Senen; A.P. Bayuseno (TEKNIK, 2012)
The train is currently trusted by the people of Indonesia as a cheap and safe means of transportation. One fromthat must be met by a train is a reliable braking system. Generally the train brake block material is used graycast iron brake block.One of materials based composite as a substitute for train brake block are the Al-SiC (Aluminium SilicaCarbida). The Al-SiC composite material has hard and soft properties. Aluminium (Al) as a matrix and SiC asreinforcement. Metal material composite used for the reseach is Al-SiC composite with composition of SiC 15%,10%, and 15% made through a process of stir casting. The specimens were tested tensile strength and impacttests. The test of results : tensile test for cast iron = 188.56 MPa; aluminium = 131.97 MPa; Al-SiC 5% =127.17 MPa, 10% = 136.41 MPa dan 15% = 107.26 MPa. The result of the energy absorbed of impact test arecast iron = 2.17 Joule; aluminium = 8.67 Joule; Al-SiC 5% = 4.00 Joule, 10% = 4.67 Joule and 15% = 2.83Joule.From the result of test, so replacement of cast iron brake material block is composite brake material block witha composition 10% of AL-SiC.